METODE PELATIHAN GERAK DASAR RANDAI DI SANGGAR MUSEUM PERANG SINTUAK KABUPATEN PADANG PARIAMAN - Rahmayuni, Mila; Tulus Handra Kadir (Universitas Negeri Padang, 2025)
This study aims to determine and describe the Randai Basic Movement Training Method at the Sintuak War Museum Studio, Padang Pariaman Regency. The type of research used is qualitative with descriptive methods. The instruments of this research are observation and interview. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature study, observation, interviews and documentation. One of the Nagari / Villages that the researchers studied was Nagari Sintuak. Nagari Sintuak is a Nagari / Village in the Sntuak Toboh Gadang District, Padang Pariaman Regency. The results of this study indicate that the Randai Basic Movement Training Method at the Sintuak War Museum Studio uses the demonstration method and the drill or repetition method. The demonstration method is applied to provide direct examples to training members regarding basic randai movement patterns. While the drill method is used to train repetition of movements until accuracy and cohesiveness are achieved. The results of this study show that the selection of appropriate training methods greatly affects the quality of traditional arts learning outcomes.